Improving the Learning Outcomes of Class VIII Students Through the Implementation of the Project-Based Learning (PjBL) Model in Science Learning - Abidin, Moh. Zainal; Yuniawati, Arien; Handhika, Jeffry (Universitas Trunojoyo Madura, 2024)
This research aims to improve the learning outcomes of junior high school students in science learning.This research is a type of classroom action research carried out in one of the public junior high schools in the Madiun district. The study population was class VIII with class VIII E samples. The data analysis technique used was to compare learning outcomes in the pre-cycle to the next cycle. The results of the analysis showed that the project-based learning (PjBL) learning model was able to improve the cognitive learning outcomes of junior high school students. The success indicator of the study was seen in the improvement in cognitive learning outcomes of students who achieved a minimum completeness criteria (MCC) score of 75. While the tang performance indicator used in this study is the success rate of cognitive learning outcomes up to 75%, in the pre-cycle, as many as 71.43% of the total students have not reached the specified minimum completeness criteria (MCC). While the remaining 38.10% have reached minimum completeness criteria (MCC). The implementation of the project-based learning (PjBL) learning model shows an increase in student success in learning. In cycle I, the percentage of student success reached 61.9%. In the second cycle, the percentage of student success reached 76.1%, so there was an increase of 33.4%.